Raiders' ransom - Diamand, Emily (New York : Scholastic Inc., 2009)
In 22nd-century Great Britain, where climate change has caused vast flooding, the piratical Reavers kidnap the Prime Minister's daughter and thirteen-year-old Lilly Melkun, an English fisher-girl, takes her seacat on a daring rescue attempt, with a mysterious talking jewel from a past computer age tucked in her belt as ransom.
"The Times winner, Children's Fiction Competition, Chicken House"--P. [4] of Jacket.
Accelerated Reader AR
Keywords: Kidnapping -- Juvenile fiction; Pirates -- Juvenile fiction; Cats -- Juvenile fiction; Computers -- Juvenile fiction; Environmental degradation -- Juvenile fiction; Great Britain -- Juvenile fiction; Action and adventure fiction